2016
DOI: 10.1002/14651858.cd004623.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Root canal posts for the restoration of root filled teeth

Abstract: Our systematic review could not specify which type of post and core system should be used when two or three dentine walls remain. More RCTs are needed to confirm whether fibre-reinforced post and core systems are superior and to clarify the influence of the remaining tooth structure on the treatment outcome of the different post and core systems available. Well-defined inclusion criteria focusing on the number of dentine walls (two or three) should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…After cavity preparation by laser and conventional methods, a total acid etching system with 37% phosphoric acid was used, followed by use of a Clearfil Universal Bond Quick etching primer on the enamel surface. Cavity preparation by laser was followed by acid etching to reduce microleakage at the enamel-composite interface [15][16][17][18][19]. The reason for selecting only one type of adhesive system was to solely obtain a comparison of the cavity preparation techniques [20].…”
Section: Discussionmentioning
confidence: 99%
“…After cavity preparation by laser and conventional methods, a total acid etching system with 37% phosphoric acid was used, followed by use of a Clearfil Universal Bond Quick etching primer on the enamel surface. Cavity preparation by laser was followed by acid etching to reduce microleakage at the enamel-composite interface [15][16][17][18][19]. The reason for selecting only one type of adhesive system was to solely obtain a comparison of the cavity preparation techniques [20].…”
Section: Discussionmentioning
confidence: 99%
“…Root fracture is a gradual propagation of craze lines and microcracks in radicular dentin. [ 26 ] Microcracks are formed as a result of rotational forces that are being applied to canal walls. Increased incidence, reported with some rotary instrumentation techniques, is related to design features of rotary instruments such as tip size, cross-sectional geometry, pitch, and taper.…”
Section: Discussionmentioning
confidence: 99%
“…However, long‐term clinical studies found no differences in clinical longevity between metal posts and PFPs with comparable failure patterns (Bolla et al, 2007; Figueiredo et al, 2015; Marchionatti et al, 2017; Sterzenbach et al, 2012).…”
Section: Introductionmentioning
confidence: 99%